Utilization and Outcomes for Spine Surgery in the United States and Canada. Issue 19 (1st October 2019) - Cram, Peter; Landon, Bruce E.; Matelski, John; Ling, Vicki; Perruccio, Anthony V.; Paterson, J. Michael; Rampersaud, Y. Raja
Abstract : Study Design: A retrospective cohort study. Objective: The aim of this study was to examine variation in spine surgery utilization between the province of Ontario and state of New York among all patients and pre-specified patient subgroups. Summary of Background Data: Spine surgery is common and costly. Within-country variation in utilization is well studied, but there has been little exploration of variation in spine surgery utilization between countries. Methods: We used population-level administrative data from Ontario (years 2011–2015) and New York (2011–2014) to identify all adults who underwent inpatient spinal decompression or fusion surgery using relevant procedure codes. Patients were stratified according to age and surgical urgency (elective vs . emergent). We calculated standardized utilization rates (procedures per-10, 000 population per year) for each jurisdiction. We compared Ontario and New York with respect to patient demographics and the percentage of hospitals performing spine surgery. We compared utilization rates of spinal decompression and fusion surgery in Ontario and New York among all patients and after stratifying by surgical urgency and patient age. Results: Patients in Ontario were older than patients in New York for both decompression (mean age 58.8 vs . 51.3 years; P  < 0.001) and fusion (58.1 vs . 54.9; P  < 0.001). A smaller percentage of hospitals in Ontario than New York performed decompression (26.1% vs . 54.9%; P  < 0.001) or fusion (15.2% vs . 56.7%; P  < 0.001). Overall, utilization of spine surgery (decompression plus fusion) in Ontario was 6.6 procedures per-10, 000 population per-year and in New York was 16.5 per-10, 000 per-year ( P  < 0.001). Ontario-New York differences in utilization were smaller for emergent cases (2.0 per 10, 000 in Ontario vs . 2.5 in New York; P  < 0.001), but larger for elective cases (4.6 vs . 13.9; P  < 0.001). The lower utilization in Ontario was particularly large among younger patients (age <60 years). Conclusion: We found significantly lower utilization of spine surgery in Ontario than in New York. These differences should inform policy reforms in both jurisdictions. Level of Evidence: 3 Abstract : Supplemental Digital Content is available in the textSpine surgery is common and costly, but there has been little exploration of variation between countries. We used administrative data from Ontario and New York to compare spine surgery utilization rates between jurisdictions. Utilization was approximately 60% lower in Ontario with differences in utilization driven largely by lower rates of elective spine procedures among younger (age <60) patients.